Examination Anxiety as Correlate of Junior High School Pupils Academic Performance in the Effutu Municipality of Ghana - Bentil, Joseph Bentil (Advances in Social Sciences Research Journal, 2020)
This study investigated the relationship between examination anxiety and pupils’ academic performance in Junior High Schools in Effutu Municipality in the Central Region of Ghana. Grounded in Smith and Ellsworth (1987) transactional model of test-related emotions, this study adopted the cross-sectional descriptive survey design with quantitative approach where seven-hundred and forty one (741) Junior High School pupils were sampled through the multi-stage sampling technique. Closed-ended questionnaire was used to collect quantifiable data. After satisfying validity and reliability requirements, the instrument was self-administered to the participants and the data was analyzed using descriptive statistics (frequency, percentages, mean, standard deviation) and inferential statistics such as t-test, ANOVA, and Pearson Product Moment Correlation. The findings of the study revealed that generally there was high examination anxiety among the Junior High School pupils. Besides, the results showed that there was a strong and statistically significant inverse relationship between examination anxiety and pupils overall academic performance. The study further disclosed that the level of pupils and age of the pupils did not significantly affect examination anxiety. Furthermore, it was revealed that sex and type of school attended significantly influenced examination anxiety. Therefore, it is recommended among others that, the Effutu Municipal Education Directorate should as a matter of urgency design and implement programmes to reduce the high anxiety levels among pupils so as to enhance academic performance. In this direction, attention should be directed to sex and type of school attended since these two variables significantly predicted examination anxiety.